His Royal Highness Sultan Nazrin Shah reflections and recollections - Mohd. Annuar Zaini (RNS Publications, 2016)
The book, entitled 'His Royal Highness Sultan Nazrin Shah; Reflections and Recollections', was a collection of work by local and international writers whom have had the privilege of dealing and communicating with Sultan Nazrin, which included personal contacts, academicians, journalists and social activists